## ๐/๐๐ฅ[csc ๐ฅ]

### To find the derivative of csc(x), we can use the quotient rule in calculus

To find the derivative of csc(x), we can use the quotient rule in calculus.

The quotient rule states that if we have a function f(x) = g(x) / h(x), where g(x) and h(x) are both functions of x, then the derivative of f(x) with respect to x is given by:

f'(x) = [g'(x) * h(x) – g(x) * h'(x)] / (h(x))^2

In our case, g(x) = 1 and h(x) = sin(x) because csc(x) = 1/sin(x).

Using the quotient rule, we can find the derivative of csc(x) with respect to x.

First, let’s find g'(x) and h'(x):

g'(x) = 0 (since g(x) = 1 is a constant)

h'(x) = cos(x) (by differentiating sin(x) using the chain rule)

Now, applying the quotient rule, we have:

csc'(x) = [g'(x) * h(x) – g(x) * h'(x)] / (h(x))^2

= [0 * sin(x) – 1 * cos(x)] / (sin(x))^2

= -cos(x) / sin^2(x)

Simplifying further, we can rewrite the expression as:

csc'(x) = -cos(x) / sin^2(x)

= -1 / (sin(x) * sin(x))

= -1 / sin^2(x)

Therefore, the derivative of csc(x) with respect to x is -1 / sin^2(x).

## More Answers:

Step-by-Step Guide: How to Find the Derivative of tan(x) Using the Quotient RuleDerivative of cot(x) using the quotient rule: Step-by-step explanation

Derivative of sec(x) with Respect to x: Step-by-Step Calculation and Explanation